2021
DOI: 10.1007/978-3-030-85521-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Multidimensional Self-assessment for Software Process Improvement: A Pilot Tool

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…It also found that 45% of the student of Barrakpore II Block bought new smartphones for online classes, which is very low (5%) in Barasat-I Block as the socio-economic condition of the respondents was very poor there. Georgiadou et al [12] explained in their paper that how online teaching is became everything nowadays; it was a challenge for all teachers and learners also. It was tough to adopt a new teaching method overnight.…”
Section: Discussionmentioning
confidence: 99%
“…It also found that 45% of the student of Barrakpore II Block bought new smartphones for online classes, which is very low (5%) in Barasat-I Block as the socio-economic condition of the respondents was very poor there. Georgiadou et al [12] explained in their paper that how online teaching is became everything nowadays; it was a challenge for all teachers and learners also. It was tough to adopt a new teaching method overnight.…”
Section: Discussionmentioning
confidence: 99%